Andalusite silicon carbide brick for submerged arc furnace and preparation method of andalusite silicon carbide brick

By using red column silicon carbide bricks, combined with modified α-Al2O3 micropowder and zirconium doped titanium oxide, the problem of damage to the ore furnace lining in a high temperature environment is solved, the high temperature stability and corrosion resistance of the material are achieved, and the use is extended Lifespan has promoted the green development of the industry.

CN119320279APending Publication Date: 2025-01-17XINMI ZHENGXING REFRACTORY MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411447664.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The mineral hot furnace lining is easily damaged in high temperature environments. The performance of existing aluminum-silicon refractory materials is insufficient, resulting in a short service life of the furnace lining, and the temperature exceeds its tolerance range when smelting high-carbon iron chromium, which increases the risk of accidents.

Method used

Use red column silicon carbide bricks as the lining material of the ore furnace. By reasonably preparing the main and auxiliary materials, including red column, silicon carbide, modified α-Al2O3 micropowder and zirconium-doped titanium oxide, it forms high-temperature stability, erosion-resistant and anti-flushing Materials with excellent performance can obtain red-column silicon carbide bricks with excellent mechanical properties and thermal shock stability through high temperature firing.

Benefits of technology

It significantly extends the service life of the ore furnace, improves the resistance to thermal shock and corrosion, enhances the mechanical properties of the materials and the load softening temperature, is suitable for high-temperature and high-pressure environments, and promotes the green and low-carbon development of the ferroalloy metallurgy industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320279A_ABST
    Figure CN119320279A_ABST
Patent Text Reader

Abstract

The invention provides an andalusite silicon carbide brick for a submerged arc furnace and a preparation method of the andalusite silicon carbide brick, and belongs to the technical field of refractory materials. The main material comprises the following components in percentage by mass: 70-75% of andalusite with the particle size of less than 5mm, 8-12% of silicon carbide with the particle size of less than 1mm, 5-10% of white corundum and / or tabular corundum with the particle size of less than 0.074 mm, 3-5% of modified alpha-Al2O3 micro powder and 5-8% of Guangxi white mud fine powder with the particle size of less than 0.074 mm; the auxiliary material comprises the following components: binding agent dextrin, zirconium-doped titanium oxide and water, the mass of the binding agent dextrin accounts for 0.5-0.8% of the mass of the main material, the mass of the zirconium-doped titanium oxide accounts for 1-2% of the mass of the main material, and the mass of the water accounts for 3-3.5% of the mass of the main material. The method ensures that the prepared product is excellent in mechanical property and erosion resistance, good in thermal shock stability and high in refractoriness under load, and can effectively prolong the service life of the submerged arc furnace when being used for the lining of the submerged arc furnace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and particularly relates to andalusite silicon carbide bricks for submerged arc furnaces and a preparation method thereof. Background Art

[0002] Submerged arc furnace is an important equipment for producing various ferroalloys. Submerged arc furnace uses self-baking electrodes to heat the charge, reduce the metal elements from the oxide ore and smelt it. There are many kinds of ferroalloys. The working temperature of different ferroalloys is different during smelting. The properties of the molten metal and slag in the furnace are different. Their damage mechanism and damage speed are different. Therefore, it is necessary to select refractory materials with different physical and chemical properties. Usually, the furnace wall near the slag line and under the furnace bottom electrode are damaged faster. The lining materials at these locations are the most critical. Aluminum-silicon refractory materials such as clay bricks and high-aluminum bricks are commonly used lining materials for submerged arc furnaces.

[0003] In the process of ferroalloy smelting, furnace bottom burn-through is the most common production accident. The service life of the furnace lining directly determines the life of the submerged arc furnace. The reasons for the damage of the submerged arc furnace lining include the softening and melting of high-temperature refractory materials, the chemical erosion of the refractory lining by slag, molten metal and reaction atmosphere, and the mechanical scouring of the charge and slag. The coupling effect of these three aspects will accelerate the damage of the furnace lining. As submerged arc furnaces develop in the direction of large-scale, the development trend of modern submerged arc furnaces is to increase the smelting intensity of the reaction zone. The working temperature and use environment in the furnace are becoming more and more harsh. For some enterprises smelting high-carbon ferrochrome, the molten iron temperature is as high as about 1600℃. The working conditions of the furnace lining structure have approached or even exceeded the performance range that aluminum-silicon refractory materials such as clay bricks and high-alumina bricks can withstand. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the present invention provides a kind of andalusite silicon carbide brick for electric arc furnace and its preparation method, ensure that the prepared andalusite silicon carbide brick has excellent mechanical properties and high temperature physical and chemical stability, good thermal shock stability, high load softening temperature, excellent corrosion resistance and scour resistance, and is used for the lining of electric arc furnace, which can effectively extend the service life of electric arc furnace, is conducive to promoting the green and low-carbon development of ferroalloy metallurgical industry, and has significant social and economic benefits.

[0005] In order to achieve the above-mentioned object, in a first aspect, the present invention provides an andalusite silicon carbide brick for a submerged arc furnace, comprising a main material and auxiliary materials;

[0006] The main material comprises the following components in terms of mass percentage: 70-75% of andalusite with a particle size less than 5 mm, 8-12% of silicon carbide with a particle size less than 1 mm, 5-10% of white corundum and / or plate-shaped corundum with a particle size less than 0.074 mm, and modified α-Al 2 O 33-5% of micro powder and 5-8% of Guangxi white mud fine powder with a particle size less than 0.074mm;

[0007] The auxiliary material comprises components: binder dextrin, zirconium-doped titanium oxide and water, wherein the mass of the binder dextrin is 0.5-0.8% of the mass of the main material, the mass of the zirconium-doped titanium oxide is 1-2% of the mass of the main material, and the mass of water is 3-3.5% of the mass of the main material.

[0008] Furthermore, the modified α-Al 2 O 3 The preparation method of micro powder is as follows:

[0009] A1. α-Al 2 O 3 The powder was placed in a NaOH solution, stirred for 9-12 minutes, then filtered, washed with pure water for 3 times, and dried in an oven at 105-110°C to obtain alkali-washed α-Al 2 O 3 Micro powder;

[0010] A2, the alkali-washed α-Al 2 O 3 The micro powder and stearylamine are mixed in a mass ratio of 100:(15-17), then placed in a 3-fold volume of toluene medium, heated to 70-85°C, stirred for 3 hours, filtered after cooling, repeatedly rinsed with toluene to remove the unabsorbed stearylamine, and dried to obtain the modified α-Al 2 O 3 Micro powder.

[0011] Furthermore, in A1, the concentration of the NaOH solution is 1 mol / L.

[0012] Furthermore, the preparation method of the zirconium-doped titanium oxide is as follows:

[0013] B1. Prepare 5% volume concentration of HNO 3 solution and 65% volume concentration of ZrO(NO 3 ) 2 Aqueous solution, then prepare Ti(OBu) 4 n-Butanol solution, cooled to 0℃ in an ice bath; Ti(OBu) 4 The volume ratio of each component in the n-butanol solution is n-butanol: Ti(OBu) 4 :H 2 O=20:4:0.65;

[0014] B2, take HNO obtained in B1 3 solution and ZrO(NO 3 ) 2 The solution was added dropwise to Ti(OBu) 4In the n-butanol solution, the three were mixed in equal volumes and stirred magnetically at 0°C for 0.5 h, and then the mixture was placed in a water bath at a relative temperature of 45°C for 8 h to obtain a transparent gel;

[0015] B3. Dry the transparent gel obtained in B2 at 120°C for 24 hours to obtain gel particles. Calcine the gel particles at 430°C, 530°C and 630°C for 8 hours each to obtain powder, which is zirconium-doped titanium oxide.

[0016] Furthermore, the andalusite with a particle size less than 5 mm is composed of andalusites with a particle size of 3-5 mm, a particle size of 1-3 mm, a particle size of 0-1 mm and a particle size less than 0.088 mm in a mass ratio of 1: (2-3): (0.5-1): (1-2).

[0017] Furthermore, the silicon carbide with a particle size less than 1 mm is composed of silicon carbide with a particle size of 0-1 mm and silicon carbide with a particle size less than 0.074 mm in a mass ratio of (1-2): (1-2).

[0018] Furthermore, the binder dextrin is yellow dextrin.

[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned andalusite silicon carbide brick for a submerged arc furnace, comprising the following steps:

[0020] S1, using a mixer to mix the main ingredient components and the auxiliary ingredient components to obtain a mixed material;

[0021] S2, using a press to press the mixed material obtained in S1 into a shape to obtain a brick;

[0022] S3. Dry the bricks obtained in S2 with a dryer until the residual moisture is less than 0.5%, place the bricks in a high-temperature tunnel kiln for firing, and cool them after firing to obtain andalusite silicon carbide bricks.

[0023] Furthermore, in S2, the pressure of the press is 630 tons.

[0024] Furthermore, in S3, the sintering temperature is 1450-1550°C, and the holding time under the sintering temperature condition is 6-10 hours.

[0025] This application has the following beneficial effects:

[0026] 1. The present invention uses high-purity andalusite as the main raw material. At high temperature, andalusite is transformed into mullite. Most of the glass phase quartz generated by the transformation of andalusite is embedded between mullite crystals. Under high temperature conditions, the glass phase in the softened or liquefied mullite crystal absorbs the volume change of mullite through elastic deformation. Therefore, the mullite transformed from andalusite has better high temperature stability and thermal shock resistance than mullite prepared from other raw materials.

[0027] Silicon carbide has the characteristics of high hardness and erosion resistance (Mohs hardness 9-9.5), high thermal conductivity, small thermal expansion coefficient, etc. It also has excellent properties such as corrosion resistance, oxidation resistance and high high-temperature strength. The present invention introduces silicon carbide to increase the anti-erosion ability of the product and improve its thermal shock stability; at the same time, the oxidation of silicon carbide is utilized to form a self-protection effect of a high-viscosity oxide film on the surface, which blocks the pores and slows down the erosion of the material.

[0028] Zirconium-doped titanium oxide increases the product's anti-erosion ability and improves its thermal shock stability; at the same time, it forms a self-protective zirconium oxide protective film on the surface through oxidation, which blocks the pores and slows down the erosion of the material.

[0029] Modified α-Al 2 O 3 The micro powder makes its surface lipophilic, avoiding the modification of α-Al 2 O 3 Micro powder agglomerates in a water environment, which helps to increase the α-Al 2 O 3 The dispersion and stability in the matrix material can better play its reinforcing role; modified α-Al 2 O 3 The micro powder fills the gaps between particles and increases the density of the material; modified α-Al 2 O 3 The silicon dioxide produced by the mullite transformation of corundum and Guangxi white mud and andalusite and the oxidation of silicon carbide further undergoes mullite reaction. The volume expansion caused by the primary mullite and secondary mullite fills part of the pores and reduces the pore diameter. The generated needle-shaped mullite forms a cross-network structure, which not only increases the strength of the product, increases the load softening temperature of the product, but also improves the thermal shock stability of the product. In particular, the mullite and secondary mullite continue during high-temperature use, giving the product better creep resistance.

[0030] 2. Zirconium-doped titanium oxide and modified α-Al 2 O 3The formation of a stable phase interface between the micropowders helps to improve the thermal shock resistance and corrosion resistance of the composite material. At high temperatures, a stable chemical bond is formed between zirconium-doped titanium oxide and silicon carbide, which enhances the internal bonding force of the material and improves its corrosion resistance; at high temperatures, the zirconium element in zirconium-doped titanium oxide reacts with the oxygen atoms in aluminum oxide and silicon oxide to form a solid solution. This substitution causes part of the atoms in the crystal structure to be replaced by zirconium atoms, thereby changing the chemical composition and physical properties of the crystal; at high temperatures, zirconium elements can also react with aluminum oxide and silicon oxide to form new compound phases, such as zirconium oxide, etc. The formation of solid solutions and new compound phases helps to reduce the pores inside the material and improve its density; the presence of solid solutions and new compound phases inhibits the growth of grains and maintains the fine-grained structure of the material, and the fine-grained structure has higher mechanical strength (compressive strength and flexural strength). BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 , a comparative trend chart of compressive strength test data of products obtained in Examples 1-5 of the present invention and Comparative Examples 1-5;

[0032] Figure 2 , a comparative trend chart of the flexural strength test data of the products obtained in Examples 1-5 of the present invention and Comparative Examples 1-5;

[0033] Figure 3 , a comparative trend chart of thermal shock stability test data of products obtained from Examples 1-5 of the present invention and Comparative Examples 1-5;

[0034] Figure 4 , a comparative trend chart of average erosion depth test data of products obtained from Examples 1-5 of the present invention and Comparative Examples 1-5;

[0035] Figure 5 , a comparative trend chart of the volume density and apparent porosity test data of the products obtained in Examples 1-5 of the present invention and Comparative Examples 1-5. DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the embodiments.

[0037] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0038] The Al in andalusite used in the present invention 2 O 3 The mass percentage of Fe is ≥58%, 2 O 3 The mass percentage of R 2 The mass percentage of O is ≤0.4%. The mass percentage of SiC in the silicon carbide used is ≥97%, and the mass percentage of Fe 2 O 3The mass percentage of Al in the plate-shaped corundum used is ≤0.7%. 2 O 3 The mass percentage of Fe is ≥99.3%, 2 O 3 The mass percentage of Na is ≤0.7%, 2 The mass percentage of O is ≤0.3%. 2 0 3 Micro powder A1 2 O 3 The mass percentage of A1 in Guangxi white mud fine powder is ≥99%. 2 O 3 The mass percentage of Fe is ≥36%, 2 O 3 The mass percentage is ≤1.0%.

[0039] Specific procurement situation: Andalusite was purchased from Lingshou County Baifeng Mineral Products Processing Plant. Silicon carbide and plate-shaped corundum were purchased from Zhengzhou Haixu Abrasive Co., Ltd. Guangxi white mud fine powder, model Nntd5656, fineness 200 mesh, was purchased from Nanning Tudun Mining Co., Ltd. α-Al 2 O 3 Micro powder was purchased from Zhengzhou Yufa High-tech Materials Co., Ltd. Stearylamine (octadecylamine) was purchased from Shandong Jinyu Chemical Co., Ltd. Ti(OBu) 4 (Tetrabutyl titanate) was purchased from Shandong Xinrongxin Chemical Technology Co., Ltd. Yellow dextrin (superior grade, content ≥ 92%) was purchased from Gongyi Renyi Refractory Materials Co., Ltd.

[0040] Example 1: (1) Preparation of modified α-Al 2 O 3 Micro powder, the preparation method is as follows:

[0041] A1. α-Al 2 O 3 The powder was immersed in a 1 mol / L NaOH solution, stirred at 120 r / min for 10 min, filtered, washed with pure water for 3 times, and dried in an oven at 108 °C for 30 min to obtain alkaline washed α-Al 2 O 3 Micro powder.

[0042] A2, the alkali-washed α-Al 2 O 3 The micro powder and stearylamine are mixed in a mass ratio of 100:(15-17), then placed in a 3-fold volume of toluene medium, heated to 70-85°C, stirred for 3 hours, filtered after cooling, repeatedly rinsed with toluene to remove the unabsorbed stearylamine, and dried to obtain the modified α-Al 2 O3 Micro powder.

[0043] (2) Prepare zirconium-doped titanium oxide, the preparation method is as follows:

[0044] B1. Prepare 5% volume concentration of HNO 3 solution and 65% volume concentration of ZrO(NO 3 ) 2 Aqueous solution, then prepare Ti(OBu) 4 n-Butanol solution, cooled to 0℃ in an ice bath; Ti(OBu) 4 The volume ratio of each component in the n-butanol solution is n-butanol: Ti(OBu) 4 :H 2 O=20:4:0.65.

[0045] B2, take HNO obtained in B1 3 solution and ZrO(NO 3 ) 2 The solution was added dropwise to Ti(OBu) 4 In the n-butanol solution, the three were mixed in equal volumes and stirred magnetically at 200 r / min for 0.5 h at 0°C to obtain a mixed solution, which was then placed in a water bath at a relative temperature of 45°C for 8 h to obtain a transparent gel.

[0046] B3. Dry the transparent gel obtained in B2 at 120°C for 24 hours to obtain gel particles. Calcine the gel particles at 430°C, 530°C and 630°C for 8 hours each to obtain powder, which is zirconium-doped titanium oxide.

[0047] (3) A method for preparing andalusite silicon carbide bricks for a submerged arc furnace, comprising the following steps:

[0048] S1. Use a mixer to mix the main material and the auxiliary material at a stirring speed of 400r / min for 10min to obtain a mixed material.

[0049] The main materials are calculated by mass percentage and include the following components: 72% andalusite with a particle size less than 5 mm, 10% silicon carbide with a particle size less than 1 mm, 8% plate-shaped corundum with a particle size less than 0.074 mm, and modified α-Al 2 O 3 4% of micro powder and 6% of Guangxi white mud fine powder with particle size less than 0.074mm.

[0050] Among them, andalusite with a particle size of less than 5 mm is composed of andalusite with a particle size of 3 to 5 mm, a particle size of 1 to 3 mm, a particle size of 0 to 1 mm, and a particle size of less than 0.088 mm in a mass ratio of 1:2.5:0.7:1.5. Silicon carbide with a particle size of less than 1 mm is composed of silicon carbide with a particle size of 0 to 1 mm and a particle size of less than 0.074 mm in a mass ratio of 1:1.

[0051] The auxiliary materials include components: yellow dextrin, zirconium-doped titanium oxide and water, wherein the mass of yellow dextrin accounts for 0.7% of the mass of the main material, the mass of zirconium-doped titanium oxide accounts for 1.5% of the mass of the main material, and the mass of water accounts for 3.2% of the mass of the main material.

[0052] S2. Use a press to press the mixed material obtained in S1 into shape. The pressure of the press is 630 tons to obtain a brick.

[0053] S3. Dry the bricks obtained in S2 with a dryer until the residual moisture is less than 0.5%, and then place the bricks in a high-temperature tunnel kiln for firing. The firing temperature is 1500°C. The heat preservation time is 8 hours under the firing temperature condition. After the firing is completed, cool the bricks to obtain andalusite silicon carbide bricks.

[0054] The relevant performance test data of the andalusite silicon carbide brick for submerged arc furnace prepared in this example are shown in Table 1.

[0055] Testing basis: "GB / T2997-2015 Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products", "GB / T30873-2014 Test method for thermal shock resistance of refractory materials", "GB / T3002-2017 Test method for high temperature flexural strength of refractory materials" and "GB / T5072-2008 Test method for compressive strength of refractory materials at room temperature".

[0056] The inventors also tested the anti-slag erosion performance in the following manner: 50 g of ferrochrome slag powder with a particle size of ≤0.074 mm was weighed and filled into a processing container made of andalusite silicon carbide bricks for the ore-fired furnace obtained in this embodiment, and then kept warm at 1650°C for 3 hours, and then cooled with the furnace, and then the processing container was cut open along the axial direction, the erosion of the processing container by the steel slag was observed and measured, and the average erosion depth (mm) was recorded truthfully.

[0057] Table 1. Relevant performance test data of the product obtained in Example 1

[0058] <![CDATA[Bulk density g / cm 3 > 2.60 Apparent porosity% 15.9 Compressive strength MPa 109.8 Flexural strength MPa 18.1 <![CDATA[Softening temperature under load (T 0.6 ) °C]]> >1700 Thermal shock stability (1100℃, water cooling) 15 Average erosion depth mm 1.2

[0059] Example 2: The difference between this example and Example 1 is that: (3) A method for preparing andalusite silicon carbide bricks for a submerged arc furnace comprises the following steps:

[0060] S1. Use a mixer to mix the main material and the auxiliary material at a stirring speed of 400r / min for 10min to obtain a mixed material.

[0061] The main materials are calculated by mass percentage and include the following components: 71% andalusite with a particle size less than 5 mm, 9% silicon carbide with a particle size less than 1 mm, 8% plate-shaped corundum with a particle size less than 0.074 mm, and modified α-Al 2 O3 4% of micro powder and 8% of Guangxi white mud fine powder with particle size less than 0.074mm.

[0062] Among them, andalusite with a particle size of less than 5 mm is composed of andalusite with a particle size of 3 to 5 mm, a particle size of 1 to 3 mm, a particle size of 0 to 1 mm, and a particle size of less than 0.088 mm in a mass ratio of 1:2.2:0.6:1.2. Silicon carbide with a particle size of less than 1 mm is composed of silicon carbide with a particle size of 0 to 1 mm and a particle size of less than 0.074 mm in a mass ratio of 1:2.

[0063] The auxiliary materials include components: yellow dextrin, zirconium-doped titanium oxide and water, wherein the mass of yellow dextrin accounts for 0.6% of the mass of the main material, the mass of zirconium-doped titanium oxide accounts for 1.4% of the mass of the main material, and the mass of water accounts for 3.3% of the mass of the main material.

[0064] S2. Use a press to press the mixed material obtained in S1 into shape. The pressure of the press is 630 tons to obtain a brick.

[0065] S3. Dry the bricks obtained in S2 with a dryer until the residual moisture is less than 0.5%, and then place the bricks in a high-temperature tunnel kiln for firing. The firing temperature is 1450°C. The heat preservation time is 6 hours under the firing temperature condition. After the firing is completed, cool the bricks to obtain andalusite silicon carbide bricks.

[0066] The relevant performance test data of the andalusite silicon carbide brick for submerged arc furnace prepared in this example are shown in Table 2.

[0067] Table 2. Relevant performance test data of the products obtained in Example 2

[0068] <![CDATA[Volume density g / cm 3 > 2.62 Apparent porosity% 15.5 Compressive strength MPa 106.6 Flexural strength MPa 18.70 <![CDATA[Softening temperature under load (T 0.6 ) °C]]> >1700 Thermal shock stability (1100℃, water cooling) 16 Average erosion depth mm 1.0

[0069] Example 3: The difference between this example and Example 1 is that: (3) A method for preparing andalusite silicon carbide bricks for a submerged arc furnace comprises the following steps:

[0070] S1. Use a mixer to mix the main material and the auxiliary material at a stirring speed of 400 r / min for 11 min to obtain a mixed material.

[0071] The main materials are calculated by mass percentage and include the following components: 73% andalusite with a particle size less than 5 mm, 10% silicon carbide with a particle size less than 1 mm, 8% plate-shaped corundum with a particle size less than 0.074 mm, and modified α-Al 2 O 3 4% of micro powder and 5% of Guangxi white mud fine powder with particle size less than 0.074mm.

[0072] Among them, andalusite with a particle size of less than 5 mm is composed of andalusite with a particle size of 3 to 5 mm, a particle size of 1 to 3 mm, a particle size of 0 to 1 mm, and a particle size of less than 0.088 mm in a mass ratio of 1:3:1:2. Silicon carbide with a particle size of less than 1 mm is composed of silicon carbide with a particle size of 0 to 1 mm and a particle size of less than 0.074 mm in a mass ratio of 2:1.

[0073] The auxiliary materials include components: yellow dextrin, zirconium-doped titanium oxide and water, wherein the mass of yellow dextrin is 0.8% of the mass of the main material, the mass of zirconium-doped titanium oxide is 2% of the mass of the main material, and the mass of water is 3.5% of the mass of the main material.

[0074] S2. Use a press to press the mixed material obtained in S1 into shape. The pressure of the press is 630 tons to obtain a brick.

[0075] S3. Dry the bricks obtained in S2 with a dryer until the residual moisture is less than 0.5%, and then place the bricks in a high-temperature tunnel kiln for firing. The firing temperature is 1550°C. The heat preservation time is 10 hours under the firing temperature condition. After the firing is completed, cool the bricks to obtain andalusite silicon carbide bricks.

[0076] The relevant performance test data of the andalusite silicon carbide brick for submerged arc furnace prepared in this example are shown in Table 3.

[0077] Table 3. Relevant performance test data of the products obtained in Example 3

[0078] <![CDATA[Bulk density g / cm 3 > 2.64 Apparent porosity% 15.3 Compressive strength MPa 111.7 Flexural strength MPa 18.6 <![CDATA[Softening temperature under load (T 0.6 ) °C]]> >1700 Thermal shock stability (1100℃, water cooling) 17 Average erosion depth mm 1.2

[0079] Example 4: The difference between this example and Example 1 is that: (3) A method for preparing andalusite silicon carbide bricks for a submerged arc furnace comprises the following steps:

[0080] S1. Use a mixer to mix the main material and the auxiliary material at a stirring speed of 400r / min for 12min to obtain a mixed material.

[0081] The main materials are calculated by mass percentage and include the following components: 70% andalusite with a particle size less than 5 mm, 8% silicon carbide with a particle size less than 1 mm, 10% plate-shaped corundum with a particle size less than 0.074 mm, and modified α-Al 2 O 3 5% of micro powder and 7% of Guangxi white mud fine powder with particle size less than 0.074mm.

[0082] Among them, andalusite with a particle size of less than 5 mm is composed of andalusite with a particle size of 3 to 5 mm, a particle size of 1 to 3 mm, a particle size of 0 to 1 mm, and a particle size of less than 0.088 mm in a mass ratio of 1:3:0.5:1. Silicon carbide with a particle size of less than 1 mm is composed of silicon carbide with a particle size of 0 to 1 mm and a particle size of less than 0.074 mm in a mass ratio of 1:1.5.

[0083] The auxiliary materials include components: yellow dextrin, zirconium-doped titanium oxide and water, wherein the mass of yellow dextrin accounts for 0.6% of the mass of the main material, the mass of zirconium-doped titanium oxide accounts for 1.2% of the mass of the main material, and the mass of water accounts for 3.1% of the mass of the main material.

[0084] S2. Use a press to press the mixed material obtained in S1 into shape. The pressure of the press is 630 tons to obtain a brick.

[0085] S3. Dry the bricks obtained in S2 with a dryer until the residual moisture is less than 0.5%, and then place the bricks in a high-temperature tunnel kiln for firing. The firing temperature is 1520°C. The heat preservation time is 9 hours under the firing temperature condition. After the firing is completed, cool the bricks to obtain andalusite silicon carbide bricks.

[0086] The relevant performance test data of the andalusite silicon carbide brick for submerged arc furnace prepared in this example are shown in Table 4.

[0087] Table 4. Relevant performance test data of the product obtained in Example 4

[0088]

[0089]

[0090] Example 5: The difference between this example and Example 1 is that: (3) A method for preparing andalusite silicon carbide bricks for a submerged arc furnace comprises the following steps:

[0091] S1. Use a mixer to mix the main material and the auxiliary material at a stirring speed of 400r / min for 10min to obtain a mixed material.

[0092] The main materials are calculated by mass percentage and include the following components: 75% andalusite with a particle size less than 5 mm, 8% silicon carbide with a particle size less than 1 mm, 5% plate-shaped corundum with a particle size less than 0.074 mm, and modified α-Al 2 O 3 5% of micro powder and 7% of Guangxi white mud fine powder with particle size less than 0.074mm.

[0093] Among them, andalusite with a particle size of less than 5 mm is composed of andalusite with a particle size of 3 to 5 mm, a particle size of 1 to 3 mm, a particle size of 0 to 1 mm, and a particle size of less than 0.088 mm in a mass ratio of 1:2.5:0.8:1.6. Silicon carbide with a particle size of less than 1 mm is composed of silicon carbide with a particle size of 0 to 1 mm and a particle size of less than 0.074 mm in a mass ratio of 1.3:1.7.

[0094] The auxiliary materials include components: yellow dextrin, zirconium-doped titanium oxide and water, wherein the mass of yellow dextrin is 0.8% of the mass of the main material, the mass of zirconium-doped titanium oxide is 1% of the mass of the main material, and the mass of water is 3% of the mass of the main material.

[0095] S2. Use a press to press the mixed material obtained in S1 into shape. The pressure of the press is 630 tons to obtain a brick.

[0096] S3. Dry the bricks obtained in S2 with a dryer until the residual moisture is less than 0.5%, and then place the bricks in a high-temperature tunnel kiln for firing. The firing temperature is 1530°C. The heat preservation time is 8 hours under the firing temperature condition. After the firing is completed, cool the bricks to obtain andalusite silicon carbide bricks.

[0097] The relevant performance test data of the andalusite silicon carbide brick for submerged arc furnace prepared in this example are detailed in Table 5.

[0098] Table 5. Relevant performance test data of the product obtained in Example 5

[0099] <![CDATA[Volume density g / cm 3 > 2.57 Apparent porosity% 16.0 Compressive strength MPa 110.2 Flexural strength MPa 17.8 <![CDATA[Softening temperature under load (T 0.6 ) °C]]> >1700 Thermal shock stability (1100℃, water cooling) 15 Average erosion depth mm 1.3

[0100] Comparative Example 1: The difference between this comparative example and Example 1 is that: the modified α-Al 2 O 3 Micro powder replaced by α-Al 2 O 3 Micro powder.

[0101] Comparative Example 2: The difference between this comparative example and Example 1 is that the modified α-Al 2 O 3 Micro powder.

[0102] Comparative Example 3: The difference between this comparative example and Example 1 is that zirconium-doped titanium oxide is deleted.

[0103] Comparative Example 4: The difference between this comparative example and Example 1 is that the modified α-Al 2 O 3 Micro powder replaced by α-Al 2 O 3 Micro powder, and delete zirconium-doped titanium oxide.

[0104] Comparative Example 5: The difference between this comparative example and Example 1 is that the modified α-Al 2 O 3 Micronized and zirconium-doped titanium oxide.

[0105] The relevant performance test data of the products prepared in Comparative Examples 1 to 5 are detailed in Table 6.

[0106] Table 6. Relevant performance test data of the products obtained from Comparative Examples 1 to 5

[0107]

[0108] Result analysis: Analyze examples 1-5 and combine the data in Tables 1-5 and Figure 1-5It can be seen that the product of the present invention has excellent mechanical properties and corrosion resistance, good thermal shock stability, and high load softening temperature. Specifically, in terms of mechanical properties, the compressive strength is as high as 106.6MPa or more, and the flexural strength is as high as 17.8MPa or more. In terms of corrosion resistance, the average corrosion depth tested by the method of the present invention is as low as less than 1.3mm. The thermal shock stability (1100℃, water cooling) test data is as high as more than 15 times. The load softening temperature is greater than 1700℃.

[0109] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Table 6 with Figure 1-5 It can be seen that when preparing the andalusite silicon carbide bricks for the submerged arc furnace of the present invention, α-Al 2 O 3 The addition of α-Al can improve the mechanical properties (compressive strength and flexural strength), load softening temperature and thermal shock stability of the product. 2 O 3 The modified α-Al 2 O 3 , can further improve the mechanical properties (compressive strength and flexural strength), load softening temperature and thermal shock stability of the product. The addition of zirconium-doped titanium oxide can improve the thermal shock stability and corrosion resistance of the product. 2 O 3 When added together with zirconium-doped titanium oxide, the two work synergistically to improve the mechanical properties (compressive strength and flexural strength), thermal shock stability and corrosion resistance of the product. 2 O 3 The modified α-Al 2 O 3 , the synergistic effect is further improved.

[0110] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0111] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A andalusite silicon carbide brick for a submerged arc furnace, characterized in that: Including main ingredients and auxiliary ingredients; The main material comprises, by mass percentage, 70-75% of andalusite with a particle size of less than 5 mm, 8-12% of silicon carbide with a particle size of less than 1 mm, 5-10% of white corundum and / or plate-shaped corundum with a particle size of less than 0.074 mm, 3-5% of modified α-Al2O3 powder, and 5-8% of Guangxi white mud fine powder with a particle size of less than 0.074 mm; The auxiliary material comprises components: binder dextrin, zirconium-doped titanium oxide and water, wherein the mass of the binder dextrin is 0.5-0.8% of the mass of the main material, the mass of the zirconium-doped titanium oxide is 1-2% of the mass of the main material, and the mass of water is 3-3.5% of the mass of the main material.

2. The andalusite silicon carbide brick for submerged arc furnace according to claim 1, characterized in that: The preparation method of the modified α-Al2O3 micropowder is as follows: A1. Place α-Al2O3 powder in NaOH solution, stir for 9-12 minutes, filter, wash with water, and dry to obtain alkali-washed α-Al2O3 powder; A2. Mix the alkali-washed α-Al2O3 micropowder obtained in A1 with stearylamine in a mass ratio of 100:(15-17), then place it in a 3-fold volume of toluene medium, heat it to 70-85°C, stir it for 3 hours, filter it after cooling, rinse it with toluene, and dry it to obtain the modified α-Al2O3 micropowder.

3. The andalusite silicon carbide brick for submerged arc furnace according to claim 2, characterized in that: In A1, the concentration of NaOH solution is 1 mol / L.

4. The andalusite silicon carbide brick for submerged arc furnace according to claim 1, characterized in that: The preparation method of the zirconium-doped titanium oxide is as follows: B1. Prepare a 5% volume concentration HNO3 solution and a 65% volume concentration ZrO(NO3)2 aqueous solution, and then prepare a Ti(OBu)4 n-butanol solution, and cool to 0°C in an ice bath; the volume ratio of each component in the Ti(OBu)4 n-butanol solution is n-butanol: Ti(OBu)4: H2O = 20:4:0.65; B2, take the HNO3 solution and ZrO(NO3)2 solution obtained in B1 and add them dropwise to the Ti(OBu)4 n-butanol solution, with equal volumes, stir at 0℃ for 0.5h, then put them in a 45℃ water bath and leave them for 8h to obtain a transparent gel; B3. Dry the transparent gel obtained in B2 at 120°C for 24 hours, and then calcine it at 430°C, 530°C and 630°C for 8 hours each to obtain a powder, namely zirconium-doped titanium oxide.

5. The andalusite silicon carbide brick for submerged arc furnace according to claim 1, characterized in that: The andalusite with a particle size less than 5 mm is composed of andalusites with a particle size of 3-5 mm, a particle size of 1-3 mm, a particle size of 0-1 mm and a particle size less than 0.088 mm in a mass ratio of 1: (2-3): (0.5-1): (1-2).

6. The andalusite silicon carbide brick for submerged arc furnace according to claim 1, characterized in that: The silicon carbide with a particle size less than 1 mm is composed of silicon carbide with a particle size of 0-1 mm and silicon carbide with a particle size less than 0.074 mm in a mass ratio of (1-2): (1-2).

7. The andalusite silicon carbide brick for submerged arc furnace according to claim 1, characterized in that: The binder dextrin is yellow dextrin.

8. A method for preparing andalusite silicon carbide bricks for submerged arc furnace according to any one of claims 1 to 7, characterized in that: The steps include: S1, using a mixer to mix the main ingredient components and the auxiliary ingredient components to obtain a mixed material; S2, using a press to press the mixed material obtained in S1 into a shape to obtain a brick; S3. Dry the bricks obtained in S2 to a moisture content of less than 0.5% using a dryer, place the bricks in a high-temperature tunnel kiln for firing, and cool them after firing to obtain andalusite silicon carbide bricks.

9. The method for preparing andalusite silicon carbide bricks for submerged arc furnace according to claim 8, characterized in that: In S2, the press force is 630 tons.

10. The method for preparing andalusite silicon carbide bricks for submerged arc furnace according to claim 8, characterized in that: In S3, the sintering temperature is 1450-1550°C, and the holding time at the sintering temperature is 6-10 hours.

Citation Information

Patent Citations

  • High strength and high thermal shock alumina bubble brick and preparation method thereof

    CN103708841A

  • Sialon combined andalusite / SiC composite refractory and preparation method thereof

    CN104003737A

  • High-performance andalusite silicon-carbide kilneye castable and preparation application method thereof

    CN105130465A

  • Brick for hot blast stove with high thermal shock resistance and low creep and manufacturing method of brick

    CN110105059A

  • Alumina hollow ball brick and preparation method thereof

    CN110423104A